Representation and reality - Putnam, Hilary (Representation and mind., 1988)
Hilary Putnam, who may have been the first philosopher to advance the notion that the computer is an apt model for the mind, takes a radically new view of his own theory of functionalism in this book. Putnam argues that in fact the computational analogy cannot answer the important questions about the nature of such mental states as belief, reasoning, rationality, and knowledge that lie at the heart of the philosophy of mind.